2007
DOI: 10.1124/dmd.107.017269
|View full text |Cite
|
Sign up to set email alerts
|

The UDP-Glucuronosyltransferase 2B7 Isozyme Is Responsible for Gemfibrozil Glucuronidation in the Human Liver

Abstract: ABSTRACT:Gemfibrozil, a fibrate hypolipidemic agent, is eliminated in humans by glucuronidation. A gemfibrozil glucuronide has been reported to show time-dependent inhibition of cytochrome P450 2C8. Comprehensive assessment of the drug interaction between gemfibrozil and cytochrome P450 2C8 substrates requires a clear understanding of gemfibrozil glucuronidation. However, the primary UDPglucuronosyltransferase (UGT) isozymes responsible for gemfibrozil glucuronidation remain to be determined. Here, we identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 22 publications
3
48
0
Order By: Relevance
“…In addition, the K m values of PAL of both M-1 and M-2 with rUGT1A6 were similar to those with rUGT1A9, but the values in rUGT1A6 and rUGT1A9 systems were both relatively lower than those in HLMs. It has been reported that K m values of some substrates in rUGT isozyme systems are somewhat lower than those in HLMs Mano et al, 2007). Because the intrinsic clearance (CL int , calculated as V max /K m ) directly reflects the capability of eliminating chemicals of enzymes (De Buck and Mackie, 2007), we calculated the CL int of PAL to M-1 and M-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the K m values of PAL of both M-1 and M-2 with rUGT1A6 were similar to those with rUGT1A9, but the values in rUGT1A6 and rUGT1A9 systems were both relatively lower than those in HLMs. It has been reported that K m values of some substrates in rUGT isozyme systems are somewhat lower than those in HLMs Mano et al, 2007). Because the intrinsic clearance (CL int , calculated as V max /K m ) directly reflects the capability of eliminating chemicals of enzymes (De Buck and Mackie, 2007), we calculated the CL int of PAL to M-1 and M-2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the identification of drug-metabolizing enzymes will be helpful for elucidating the role of these particular enzymes in drug-drug interactions and evaluating the impact of genetic polymorphisms associated with the enzymes of interest. Currently, the strategies for the procedures typically used for definitive cytochrome P450 reaction phenotyping have been developed for the identification of human UGTs based on the glucuronidation of endogenous and exogenous compounds in vitro (Bauman et al, 2005;Mano et al, 2007).…”
mentioning
confidence: 99%
“…UGT2B7 is an enzyme responsible for detoxification of xenobiotics, including drugs such as morphine, efavirenz, zidovudine, and fenofibric acid, and is involved in the homeostasis of endogenous molecules like eicosanoids, bile acids, and sex steroids (Jin et al, 1997;Barbier et al, 2000;Stone et al, 2003;Turgeon et al, 2003;Thibaudeau et al, 2006;Mano et al, 2007;Bélanger et al, 2009;Tojcic et al, 2009;Trottier et al, 2013). Its expression is high in liver and kidney, but is also detectable in the gastrointestinal tract and peripheral tissues (Nakamura et al, 2008;Court et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…mediate the phase II metabolism and passing through the blood-brain barrier (BBB) of morphine as well as its metabolites [17,29,30]. In our study, the concentrations of gemfibrozil, morphine, and two of its main metabolites, M3G and M6G, in different mouse brain structures including cerebrum and epencephalon, even in the refined section hippocampus, were assayed simultaneously by using SPE-UHPLC-MS/MS with the deuterated IS by positive ions and anion mode, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Mano et al reported a significant correlation between gemfibrozil and morphine 3-OH glucuronidation with an almost similar affinity to the enzyme UGT2B7. It means that gemfibrozil may experience a similar metabolic process like morphine in human beings [17]. Furthermore, as the substrates of UGT2B7, gemfibrozil can influence renal internal CL int when incubated with the naloxone, which has a same structure like morphine, so it can affect the metabolites generation and body distribution of morphine when used in combination of two drugs [18].…”
Section: Introductionmentioning
confidence: 99%